Estimation of Chromium (III) in Tannery Effluents: A Solvent Extraction Study - A. V. L. N. S. H. Hariharan; D Santhi Priya (Chemical and Materials Sciences: Developments and Innovations Vol. 6, 2024)
This present study aimed to highlight the extraction of Cr (III) by using different extraction systems. Limited work has been reported on the liquid-liquid extraction of chromium (III) due to its relatively poor extractability and its inertness, unlike other transition metals. The extraction of chromium (III) from hydrochloric, sulphuric, nitric, and perchloric acid solutions with Tributylphosphine Oxide (TBPO) in chloroform has been studied. The extractions from nitric, hydrochloric, and sulphuric acid solutions are nearly quantitative (99%) and are partial from perchloric acid solutions. The optimum conditions were evaluated by varying the experimental conditions such as pH (5.0), shaking period, concentration of metal ion, Tributylphosphine oxide (0.025M), anion, and various diluents (maximum efficiency,99% obtained with chloroform) on the extraction. The extracted species are identified as containing 3 moles of TBPO. The effect of other metal ions both in presence and absence resulted in achieving an expected outcome.